Apoptotic p53 Gene Expression in the Regulation of Persistent Organic Pollutant (POP)-Induced Oxidative Stress in the Intertidal Crab Macrophthalmusjaponicus - Kiyun Park; Ihn-Sil Kwak (MDPI AG, 2022)
Persistent organic pollutants (POPs), some of the most dangerous chemicals released into the aquatic environment, are distributed worldwide due to their environmental persistence and bioaccumulation. In the study, we investigated p53-related apoptotic responses to POPs such as hexabromocyclododecanes (HBCDs) or 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) in the mud crab Macrophthalmus japonicus. To do so, we characterized M. japonicus p53 and evaluated basal levels of p53 expression in different tissues. M. japonicus p53 has conserved amino acid residues involving sites for protein dimerization and DNA and zinc binding. In phylogenetic analysis, the homology of the deduced p53 amino acid sequence was not high (67-70%) among crabs, although M. japonicus p53 formed a cluster with one clade with p53 homologs from other crabs. Tissue distribution patterns revealed that the highest expression of p53 mRNA transcripts was in the hepatopancreas of M. japonicus crabs. Exposure to POPs induced antioxidant defenses to modulate oxidative stress through the upregulation of catalase expression. Furthermore, p53 expression was generally upregulated in the hepatopancreas and gills of M. japonicus after exposure to most concentrations of HBCD or BDE-47 for all exposure periods. In hepatopancreas tissue, significant increases in p53 transcript levels were observed as long-lasting apoptotic responses involving cellular defenses until day 7 of relative long-term exposure. The findings in this study suggest that exposure to POPs such as HBCD or BDE-47 may trigger the induction of cellular defense processes against oxidative stress, including DNA repair, cell cycle arrest, and apoptosis through the transcriptional upregulation of p53 expression in M. japonicus.